Contradictions of Imam Siddiq Khan Al- Qannuji’s Views between His Quranic Commentary & His Book on Principles of Islamic Jurisprudence: Deduction & Specification of Quran & Sunnah as a Model - ESHARIF, MUSTAFA M.; MANZHOORULHAQUE, ANISURRAHMAN; DOUCOURE, ABDOU SAMADOU (Journal of Islamic Sciences, 2019)
This research aims to present Imam Siddiq Khan Akl- Qannuji as Holy Quran interpreter and as a jurist, to elucidate the value of his writings, to explain the relation between two of his books: Fath al- Bayan Fi Maqasid al_Quran and Husul al- Ma’mul Min Ilm al- Usul and to analyze the differences in his views regarding the same issue in these two books. The problem statement of this research lies in the contradiction of Imam al- Qannuhi’s views in his commentary and his book on the principles of Islamic jurisprudence. In his commentary he denied some of his views that he defended in Husul al- MA;mul which he wrote years before Fath al- bayan. Al- Qannuji didn’t attempt to justify this contrast, and he doesn’t look oblivious since he consolidated his arguments perfectly in Husul al- Ma;mul. The adapted method in this research is descriptive method based on documentation and analysis of the collected data and the deductive approach was used to figure out the opinions of Imam al- Qannuji from his commentary and other books on Islamic law and principles of Islamic jurisprudence. The researcher found that the contradiction of Imam al- Qannuji’s views related to the nature of the exegetic approach which demands variety of detailed examples for Quranic legal verses. Such detailed examples are not significant in principles of Islamic Jurisprudence. Imam al- Qannuji followed the majority of Muslim scholars in the issue of deduction and specification of Quran & Sunnah in his book Husul al- Ma’mul, but in Fath al- Bayan he disregarded that opinion, but the verses relevant to this issue and he interpreted supported his first choice due to impact of exegetic approach in his commentary.
Keywords: al- Qannuji; Siddiq Khan; Deduction; Specification; Fath al- Bayan; Husul al- Ma’mul